Analisis Komoditas Unggulan Subsektor Tanaman Pangan di Kabupaten Klungkung: Analisis Komoditas Unggulan Subsektor Tanaman Pangan di Kabupaten Klungkung - Widiastini, Anak Agung Istri Rai; Dewi, Ni Luh Prima Kemala (Journal Science Innovation and Technology (SINTECH), 2025)
Sustainable regional development is closely linked to the crucial role of economic growth. With the implementation of regional autonomy, development in each region must align with its unique potential. Klungkung Regency has experienced fluctuating economic growth, often falling below the average growth rate of Bali Province over the past five years. The agricultural sector continues to be the main driver of the economy in Klungkung Regency. This study aims to identify the patterns and structure of economic growth in the food crop subsector, assess both its comparative and competitive advantages, and explore the sustainability prospects of key food crop commodities in the region. The research methods employed include Klassen Typology, Location Quotient (LQ), Shift Share Analysis (SSA), and Dynamic Location Quotient (DLQ), using time-series data from 2019-2023. The findings indicate that the food crop subsector in Klungkung Regency is classified as an advanced and rapidly growing sector. Commodities with comparative advantages include corn, soybeans, peanuts, and cassava, while those with competitive advantages include corn, cassava, and rice. Looking ahead, corn, soybeans, and cassava are expected to remain dominant commodities, while rice is considered a staple commodity, peanuts are seen as a promising commodity, and sweet potatoes are classified as a lagging commodity